(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Description of the clinical characteristics and identification of dermatophyte species in patients with dermatophytosis attending Military Hospital 103 in 2023. Method: A cross-sectional descriptive study was conducted on 89 dermatophytosis patients using direct microscopic examination and culture of skin scales at Military Hospital 103 from January 2023 to October 2023. Species identification was performed using PCR-RFLP and sequencing of the ITS1-5.8S-ITS2 gene region. Results: The mean age of patients was 28.27 ± 13.61 years, and 84% were male. More than 92% of patients reported pruritus, 85.4% had fewer than three lesion sites, and 62.9% had lesion areas ranging from 1 to 5 palm-sized areas. Tinea corporis (75.3%) and tinea cruris (34.8%) were the most common clinical types. Lesions with well-defined borders accounted for 93.3%, erythematous lesions for 91%, scaly lesions for 86.5%, and those with central clearing for 59.6%. Among the 74 isolated strains, T. rubrum was the most prevalent species (44.6%), followed by T. interdigitale (27%), T. tonsurans (24.3%), M. canis (2.7%), and T. indotineae (1.4%). Conclusion: In dermatophytosis, annular erythematous inflammation and itching are the most dominant symptoms. Dermatophyte species mostly belong to the Trichophyton genus